دراسة سورة محمد صل الله عليه وسلم دراسة بيانية - شلبي, أشواق; صولي, شوشة (جامعة الوادي university of eloued, 2018)
الحمد تتناول هذه المذكرة دراسة سورة محمد صلى الله عليه وسلم دراسة بيانيا، وذلك للكشف عن خصوصية النص القرآني وبلاغته وفصاحة ألفاظه فلا يضع لفظة إلا في موضعها المناسب، والتعرف على أبعاده الجمالية لوقوف على كل آية من هذه السورة الكريمة اتضح لنا 􀁕 المتمثلة في دقة معانيه، وبلاغة تراكيبه، وذلك فيها أسلوب بلاغي أو لمسة بيانية أو لفظة كان لها سر في وضعها دون مرادفتها، ومن ثم إبراز ما فيها من عناصر الجمال والتأثير على المعنى، ومع هذا فقد تبين لنا أن السورة الكريمة فيها ثراء عظيم من إلا على أبرزها، 􀁡 للمسات البيانية التي اقتصر 􀁕 ا مليئة 􀁥 أقله لربما، كما أ 􀁡 الناحية البلاغية وقد ذكر وهذا وإن دل على شيء فهو يدل على عظم ما في كتاب لله تعالى من بيان وإعجاز، فهو كتاب صالح لكل زمان، قابل للبحث والنظر وفي كل رؤية جديدة تتجلى معلومات وآفاق جديدة. Reseqrch summary This memorandum dealt with the study of surat mohammed a rhetorical stdudy to reveal the specifities of the coranic text and the eloquence of its terms. Every term is placed exactly in its right place and is identified with its aesthetic dimensions into the accuracy of meanings and the eloquence of structures and that’s by pointing out every verses from this holysurat. It became obvious to us a rhetorical style and the metaphorically touch.also the secret of using a term instead of its synonym. Then ,the highlight of the elements of beauty and its influence on the meaning. Howeve, we discovered that the holy surat has a great value in the figurative language, as we have mentioned a few (Iarobama). It is also full of rhetorical touches which we limited to the most prominent.and this shows the greatness of the book of allah which is full of rhetoric and miracles. The holy coran is an adequate book fo rall time and plas. It is a searchable source in every new vision emerges new informations and new perspectives.
لغة